2012
DOI: 10.3389/fneur.2012.00122
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pediatric ASPECTS Correlates with Infarct Volume in Childhood Arterial Ischemic Stroke

Abstract: Background and Purpose: Larger infarct volume as a percent of supratentorial brain volume (SBV) predicts poor outcome and hemorrhagic transformation in childhood arterial ischemic stroke (AIS). In perinatal AIS, higher scores on a modified pediatric version of the Alberta Stroke Program Early CT Score using acute MRI (modASPECTS) predict later seizure occurrence. The objectives were to establish the relationship of modASPECTS to infarct volume in perinatal and childhood AIS and to establish the interrater reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…The Brush et al study 4 did not include data on infarct volume or BP at follow-up. Infarct volume was very strongly associated with outcome in our study population, a finding similarly reported by Ganesan et al 19 with pediatric large-vessel strokes and by Beslow et al 28 when using MRI to estimate infarct volume. Our study population included 50 children (51.0%) with cardiac disease, presumably those at high risk for hypertension.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Brush et al study 4 did not include data on infarct volume or BP at follow-up. Infarct volume was very strongly associated with outcome in our study population, a finding similarly reported by Ganesan et al 19 with pediatric large-vessel strokes and by Beslow et al 28 when using MRI to estimate infarct volume. Our study population included 50 children (51.0%) with cardiac disease, presumably those at high risk for hypertension.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, a strong association was found between large infarct volume and poor outcome, as expected. 19,28 We believe that future studies should consider infarct volume when assessing predictors associated with outcome.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Manual and automated quantification of lesion volume have also been demonstrated to be predictive of both motor and cognitive outcomes after IPS. 71,72 Extracorporeal membrane oxygenation Newborns with severe hypoxemic respiratory failure who require life support with ECMO are at high risk for neurodevelopmental compromise, attributable to both pre-ECMO hypoxic-ischemic injuries as well as hemorrhagic complications during therapy. 73 Other neuroimaging abnormalities have also been described, such as increased subarachnoid spaces and cerebral atrophy.…”
Section: Ischemic Perinatal Strokementioning
confidence: 99%
“…We selected the MCA because it is by far the most common territory for neonatal stroke, and in the mature brain it is known to contain important cortical autonomic centers, including the insula. 5 The severity of MCA stroke was classified according to the previously validated Modified Pediatric ASPECT (Alberta stroke program early CT) score 6 based on the ability of this instrument to quantify childhood arterial ischemic stroke volumes. Higher scores (maximum of 15 points per hemisphere) indicate larger areas of infarction.…”
Section: Methodsmentioning
confidence: 99%